2021
DOI: 10.1111/jvim.16122
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a flash glucose monitoring system in cats and determination of the time lag between blood glucose and interstitial glucose concentrations

Abstract: Background: The FreeStyle Libre (Abbott Laboratories) is a flash glucose monitoring system (FGMS) that measures interstitial glucose concentration (IG). The system is factory-calibrated, easy to use, inexpensive, and could be useful for monitoring diabetic cats.Objectives: To evaluate the analytical and clinical accuracy of the FGMS in cats and establish the lag-time between IG and blood glucose concentration (BG).Animals: Twenty client-owned diabetic cats and 7 purpose-bred healthy cats.Methods: Prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 32 publications
9
39
4
Order By: Relevance
“…Our recommendation would be to use cyanoacrylate to fix the sensors onto the skin. 35,37 We found a very strong positive correlation between IG and BG in the diabetic cats, similar to other studies in dogs and cats. [33][34][35][36][37] The correlation was better if the sensor was located on the thorax (r = 0.91) vs the dorsal neck (r = 0.63).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our recommendation would be to use cyanoacrylate to fix the sensors onto the skin. 35,37 We found a very strong positive correlation between IG and BG in the diabetic cats, similar to other studies in dogs and cats. [33][34][35][36][37] The correlation was better if the sensor was located on the thorax (r = 0.91) vs the dorsal neck (r = 0.63).…”
Section: Discussionsupporting
confidence: 90%
“…We found a very strong positive correlation between IG and BG in the diabetic cats, similar to other studies in dogs and cats. 33 37 The correlation was better if the sensor was located on the thorax (r = 0.91) vs the dorsal neck (r = 0.63). This difference has not been described previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With motivated owners who have a calm diabetic cat, the use of a continuous (or flash) glucose monitoring system (eg, FreeStyle Libre; Abbott Laboratories), which measures interstitial glucose, can be proposed, and the sensor applied, within the first weeks of treatment (Figure 2). 34 Aiming for normal or near-normal blood glucose concentrations is not recommended, as this increases the risk of hypoglycaemia. Most diabetic cats are considered well controlled if their blood glucose is maintained at between 80 and 200 mg/dl (4.4–11.1 mmol/l).…”
Section: Basic Principles Of the Management Of Dmmentioning
confidence: 99%
“…Continuous glucose monitoring systems (CGMSs) are frequently used in humans with diabetes, and clinical studies have shown they are effective in reducing hypoglycemia and improving glycemic control [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Thanks to their high performance, CGMSs have gained popularity among veterinarians and are increasingly being used in diabetic dogs (DD) and cats [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. CGMSs measure, using a transcutaneous sensor, interstitial glucose (IG) concentration, which reflects the blood glucose (BG) concentration [ 10 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%